Heart failure and long-term prognosis in patients with congenital heart disease: a nationwide, register-based cohort study. (3rd October 2022) - Bergh, N; Skoglund, K; Fedchenko, M; Bollano, E; Eriksson, P; Dellborg, M F; Giang Kok, W; Mandalenakis, Z
Abstract: Introduction: Heart failure (HF) is associated with high morbidity and severe prognosis. The aim of this study was to investigate the risk of HF in patients with congenital heart disease (CHD) and to determine the prognosis after HF diagnoses in patients with CHD compared to HF controls without CHD. Methods: We identified 89, 532 patients with CHD born between 1930 and 2017 from the National Patient Register in Sweden and matched with 10 controls without CHD by gender and birth year from the National Population Register. The study population was followed-up until 2017, through the Swedish Patient Register and Cause of Death Register. Results: Altogether, 7, 013 (7.8%) patients with CHD and 9, 681 (1.1%) controls developed HF. The overall incidence rate of HF was 31.6 per 104 person-years in patients with CHD and 4.0 per 104 person-years in controls. The mean age for HF diagnoses was 40.3 (± 28.8) in patients with CHD and 66.4 (± 13.6) for controls. The risk for developing HF was significantly higher in complex than non-complex CHD lesion groups, HR 28.7 (26.5–31.0) and HR 6.9 (6.7–7.2) respectively. Mortality incidence rate was twice as high in controls with HF compared to CHD with HF (IR 9.7 (9.4–10.0) and 4.74 (4.6–4.9), respectively). The mortality incidence was higher within all age groups except for 18–39 years and there was no difference between complex and non complex lesions Conclusion: One out of thirteen CHD patients will develop HF. The highest risk for HF is within CHD patients with complex lesions. CHD patients develops HF at a considerably younger age, reflecting their slightly better prognosis after development of HF compared to controls with HF. Funding Acknowledgement: Type of funding sources: None.